(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
It is very desirable to have information about the nature and structure of the active centers in order to create a catalyst of choice for the process, which has high catalytic activity and productivity for the conversion of ethyl alcohol to divinyl.